Moral signaling through donations of money and time - Johnson, Samuel G.B.; Park, Seo Young (Organizational behavior and human decision processes, 2021)
•Donations of time are seen as more virtuous than donations of money.•This occurs despite people’s (correct) belief that money-donations help more people.•The effect is driven by the perception that time-donors are more emotionally invested.•These judgments influence interpersonal attraction and donor behavior.•The findings support reputation-signaling accounts of prosocial behavior. Prosocial acts typically take the form of time- or money-donations. Do third-parties differ in how they evaluate these different kinds of donations? Here, we show that people view time-donations as more morally praiseworthy and more diagnostic of moral character than money-donations, even when the resource investment is comparable. This moral preference occurs because people perceive time-donations as signaling greater emotional investment in the cause and therefore better moral character; this occurs despite the (correct) belief that time-donations are typically less effective than money-donations (Study 1). This effect in turn is explained by two mechanisms: People believe that time-donations are costlier even when their objective costs are equated, which happens because people rely on a lay theory associating time with the self (Study 2). The more signaling power of time-donations has downstream implications for interpersonal attractiveness in a dating context (Study 3A), employment decisions (Study 3B), and donor decision-making (Study 3). Moreover, donors who are prompted with an affiliation rather (versus dominance) goal are likelier to favor time-donations (Study 4). However, reframing money-donations in terms of time (e.g., donating a week’s salary) reduced and even reversed these effects (Study 5). These results support theories of prosociality that place reputation-signaling as a key motivator of moral behavior. We discuss implications for the charity market and for social movements, such as effective altruism, that seek to maximize the social benefit of altruistic acts.